Changing Inequalities in Housing Outcomes across Western Europe. Issue 2 (2nd April 2016) - Dewilde, Caroline; De Decker, Pascal
Abstract: We evaluate to what extent the financialization of housing is associated with changing inequalities in housing outcomes for low-income owners and private renters, using data for two time points (1995 and 2012) for 11–13 western European countries. We find that in countries with a more commodified housing regime, low-income respondents experience more affordability problems (resulting in a wider gap with middle-income respondents), but better housing conditions. Concerning trends over time, we find that with regard to housing affordability, in most countries the position of low-income owners and private renters has deteriorated over time compared to their middle-income counterparts. This trend can be explained by increases in the level of financialization of housing, and decreases in the supply of private rental housing – controlling for trends in absolute incomes and income inequality. Declining affordability for low-income owners and private renters in more financialized housing regimes has furthermore not been compensated by improved housing conditions. Although it may have intensified since 2008, the observed trend does not originate from declining household incomes following the Great Financial Crisis (2008–2009), as the affordability gap between low- and middle-income private renters already grew significantly larger with the increased financialization during the period 1995–2007.